Perinatal outcomes in 521 gestations after fresh and frozen cycles: a secondary outcome of a randomized controlled trial comparing GnRH antagonist versus GnRH agonist protocols. Issue 4 (October 2019) - Tomás, Claudia; Toftager, Mette; Løssl, Kristine; Bogstad, Jeanette; Prætorius, Lisbeth; Zedeler, Anne; Bryndorf, Thue; Andersen, Anders Nyboe; Pinborg, Anja
Abstract: Research question: Are perinatal outcomes different after treatment with the gonadotrophin-releasing hormone (GnRH) antagonist versus the long GnRH agonist protocol for IVF? Design: Perinatal outcomes were secondary outcomes in a large Phase IV, dual-centre, open-label, randomized controlled trial to compare GnRH antagonist and long GnRH agonist protocols in women <40 years undergoing their first assisted reproductive technology treatment. Women ( n = 1050) were randomized in a ratio 1:1 from January 2009 to December 2013 and followed until December 2016. All fresh and frozen embryo transfer (FET) cycles from a single oocyte aspiration, resulting in a gestation (human chorionic gonadotrophin >10 IU/l) were included ( n = 521). Data were analysed to compare preterm birth [PTB] (<37 weeks), very PTB (<32 weeks), low birthweight [LBW] (<2500 g) and very LBW (<1500 g) rates among singleton live births in GnRH antagonist versus agonist protocol. Results: Similar perinatal outcomes were found after both protocols. In singletons after fresh embryo transfer, mean gestational age at delivery was 39.1 ± 2.49 versus 39.3 ± 1.90 ( P = 0.67) and very PTB rates 1.9% versus 0% ( P = 0.17). Mean birthweight was 3264 ± 662 g in the antagonist and 3341 ± 562 g in the agonist group ( P = 0.37). LBW was found in 12.4% versus 7% ( P = 0.19) and very LBW in 2.9% versus 1% ( P = 0.34). In FET cycles, the perinatal outcomes were similar. Small for gestational age and large for gestational age rates were similar in both protocols for singleton live births after fresh and FET. Conclusions: Perinatal outcomes are similar after the GnRH antagonist versus GnRH agonist protocols for IVF. The choice of the GnRH analogue in ovarian stimulation should be based solely on optimizing the chance of pregnancy and not on risks in perinatal outcomes.